2021
DOI: 10.3389/fendo.2020.614692
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Oxysterol, 7-Ketocholesterol Accelerates Hepatic Lipid Accumulation and Macrophage Infiltration in Obese Mice

Abstract: Non-alcoholic fatty liver disease is strongly associated with obese and type 2 diabetes. It has been reported that an oxidized cholesterol, 7-ketocholesterol (7KC), might cause inflammatory response in macrophages and plasma 7KC concentration were higher in patients with cardiovascular diseases or diabetes. Therefore, we have decided to test whether small amount of 7KC in diet might induce hepatic steatosis and inflammation in two types of obese models. We found that addition of 0.01% 7KC either in chow diet (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The sum of C7 cholesterol oxides (7α-HC, 7β-HC, 7-KC) in milk powders after production was 0.4 µg g −1 powder, which is consistent with the results of this study (0.3 µg g −1 powder). As recently reviewed by Chang et al 36 the addition of small quantities of dietary 7-KC contributed to accelerated hepatic steatosis and inflammation in obese mice models.…”
Section: Discussionmentioning
confidence: 83%
“…The sum of C7 cholesterol oxides (7α-HC, 7β-HC, 7-KC) in milk powders after production was 0.4 µg g −1 powder, which is consistent with the results of this study (0.3 µg g −1 powder). As recently reviewed by Chang et al 36 the addition of small quantities of dietary 7-KC contributed to accelerated hepatic steatosis and inflammation in obese mice models.…”
Section: Discussionmentioning
confidence: 83%
“…In the current study, we developed a high fat/high cholesterol/high sucrose/bile acid diet 29 . In this model, steatohepatitis was characterized by more accumulation of free cholesterol and cholesterol crystals than other steatosis models, such as ob/ob mice fed a high-fat diet 30 , thus leading to activation of the inflammasome pathway, including NLRP3 and IL-1β (Fig. 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…RT–qPCR and western blotting were performed as described previously 30 . Briefly, total RNA was isolated from liver tissues using the RNeasy® Mini Kit (QIAGEN, Hilden, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Therefore, our ndings could be translated into practice through clinical trials. Furthermore, because it has been reported that 7-KC is related to other cardiometabolic diseases, such as nonalcoholic fatty liver disease 45 and age-related macular degeneration, 46 7-KC could also be a therapeutic target in such diseases. It is noteworthy that the 7-KC level was signi cantly increased in heart tissue, not only in the blood (data not shown), and the related roles should be explored in other heart diseases.…”
Section: Discussionmentioning
confidence: 99%